Aerial video recording using helium balloon for building surveillance - Alvin David Miieg (School of Environmental Engineering, University Malaysia Perlis, 2013)
This project is made with a purpose to save cost for aerial recording. It is design mainly to monitor the site area from ground level which designed for building engineer to carry out the investigation easier.